Analysis of Madrasah Head Strategies to Develop Teacher Professionalism in Islamic Elementary School - Sutrisno, Edi; Arifah, Umi; Kurniawan, Benny; Fatimah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2025)
The success of educators in enhancing their professionalism in their duties is significantly determined by the strategies of the Madrasah Head. The Madrasah Head, as a leader, must be able to direct and provide supervision to educators in improving their professionalism. Therefore, the Madrasah Head must have strategies to enhance educator professionalism. The purpose of this research is to identify and analyze the strategies of the Madrasah Head in improving teacher professionalism at MI Ma’arif Plus Jatinegara. The method used in this research is qualitative research. The data collection techniques used in this thesis include observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman and Saldana model, which consists of four stages: data collection, data condensation, data display, and data verification. Based on the research results, it can be concluded that the strategies of the Madrasah Head in enhancing teacher professionalism include: conducting training, workshops, seminars, supervision, meetings, and further studies, as well as providing motivation, enforcing discipline, and implementing reward and punishment systems.